"Quantum-Nuclear DNA Computing: Using Nucleotide Spin States as Biological Quantum Bits for Molecular Calculations" - Barack Ndenga (Publisher, 2025)
This article explores a novel paradigm at the intersection of quantum information science and molecular biology, introducing Quantum-Nuclear DNA Computing. The central idea is to utilize the spin states of nucleotide nuclei (protons, phosphorus, and other relevant isotopes) as biological quantum bits (qubits) capable of performing molecular-scale computations. Unlike classical DNA computing, which encodes information in the base sequence, this approach leverages intrinsic quantum properties of nucleotides—particularly nuclear spin coherence, entanglement, and superposition—to achieve massively parallel information processing. The paper develops a theoretical framework for mapping nucleotide spin states to qubit representations, outlines potential mechanisms for spin manipulation and readout (via NMR, spin resonance, and quantum sensors), and discusses error correction strategies inspired by DNA’s natural redundancy. Applications are envisioned in biological data storage, cryptography, quantum simulations, and bio-inspired quantum processors. This work positions DNA not merely as a carrier of genetic information but as a living quantum register, opening pathways toward hybrid biophysical computing platforms where life’s molecular substrates and quantum mechanics converge.
This article explores a novel paradigm at the intersection of quantum information science and molecular biology, introducing Quantum-Nuclear DNA Computing. The central idea is to utilize the spin states of nucleotide nuclei (protons, phosphorus, and other relevant isotopes) as biological quantum bits (qubits) capable of performing molecular-scale computations. Unlike classical DNA computing, which encodes information in the base sequence, this approach leverages intrinsic quantum properties of nucleotides—particularly nuclear spin coherence, entanglement, and superposition—to achieve massively parallel information processing. The paper develops a theoretical framework for mapping nucleotide spin states to qubit representations, outlines potential mechanisms for spin manipulation and readout (via NMR, spin resonance, and quantum sensors), and discusses error correction strategies inspired by DNA’s natural redundancy. Applications are envisioned in biological data storage, cryptography, quantum simulations, and bio-inspired quantum processors. This work positions DNA not merely as a carrier of genetic information but as a living quantum register, opening pathways toward hybrid biophysical computing platforms where life’s molecular substrates and quantum mechanics converge.